ENGLISH OUTSIDE THE CLASSROOM IN THE AGE OF TECHNOLOGY: A CONCURRENT TRIANGULATION MIXED METHOD STUDY - Ipek, Omer Faruk; Mutlu, Hakan Tahiri (International Online Journal of Education and Teaching, 2022)
The hegemony of technology and its dominance over education caused the necessity to make changes in the philosophy of language teaching. With the introduction of technology and extensive use of distance education thanks to pandemic, this philosophy change has increased the importance of students' out-of-class language learning activities. Therefore, in this mixed method research, which is conducted at an English Preparatory department of a state university situated in Turkey, it is aimed to investigate students’ resources and strategies that they use for English outside the class (EOC) activities. For this purpose, a 34-question five-point Likert type scale was conducted to 242 students, and both focus group interviews with seven students and individual semi-structured interviews with five students were conducted in order to obtain the EOC strategies and sources. According to the results, it is revealed that the students mostly employ EOC activities for their listening skill, and least for speaking skill, and using EOC activities has a significant relationship with academic achievement, gender, and section. Also, students started to use many different technological social media websites, online applications, and techniques. As a result, with the changing educational philosophy and spending time more outside the school, all stakeholders should be aware of the massive transformation in language education and plan their instruction accordingly.